Multiple anchor delivery tool - Reich, Tal; Gross, Amir; Cabiri, Oz; Hammer, Tal; Iflah, Ehud (2020)
Anchor deployment systems and tools are provided. An anchor deployment tool can include a flexible tube including a distal anchor manipulation portion. The tool can also include a deployment element, which is positionable within the flexible tube, and is configured to, while the distal anchor manipulation portion is proximate an implantable device, (i) engage the anchors in the flexible tube, (ii) advance each of the anchors in a distal direction to the distal anchor manipulation portion, and (iii) anchor the implantable device to tissue of a subject by deploying each of the tissue anchors through the implantable device and into the tissue.